ANALISIS PENGARUH VARIASI PRODUK DAN LABELISASI HALAL TERHADAP KEPUASAN KONSUMEN UNTUK MENINGKATKAN MINAT BELI ULANG PADA KOSMETIK WARDAH - Rahmat Hidayat; Devrina Resticha (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
This research aims to examine the influence of product variation and halal labeling on consumer satisfaction to increase repurchase interest Wardah Cosmetics which is mediated by consumer satisfaction in Batam City. Data analysis technique used in this research is path analysis. The population in this research is all consumers who ever bought Wardah Cosmetics. The technique used for the sampling in this research is nonprobability sampling with the number of samples in this research was 150 respondents.The results of this research indicate that product variation and halal labeling partially have positive and significant effect on consumer satisfaction, halal labeling and consumer satisfaction partially have positive and significant effect on repurchase interest, product variation has no positive and significant effect on repurchase interest. Halal labeling and consumer satisfaction simultaneously have an effect on repurchase interest.